1996
DOI: 10.1108/09649429610117434
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of successful women managers and professionals in local government: a national survey

Abstract: Describes a survey of international City/County Management Association female members in professional, mid‐level management, and upperlevel management positions to determine the factors they see as important to their career success. The questionnaire contained measures of three models (human capital, socio‐psychological, systemic) which are cited as explanatory of the success achieved by women. The majority of women, regardless of position in the organization, attribute their success to variables that are with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…Thus, with the aim of facilitating the development of fairer employment, this paper addressed the career barriers of Arab women managers by linking several macro-level factors (most notably, the gendered national legislative systems and the intersection between Isalm, Urf and patriarchy), with organizational-level factors (e.g., governance system and HR policies and practices), and micro-level factors (e.g., women mangers' perceived traits). The findings of the present research validated the findings of Karam and Afioni (2013), Keeton (1996), Budworth and Man (2010), Metcalf (2011), the WB (2014) and UNDP (2013). Consistent with previous research findings is the analogy revealed by the present findings between the Arab women managers' challenges inside their organizations (i.e., at the mezzo level) and those facing them outside the organization (i.e., at the macro level).…”
Section: Secondsupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, with the aim of facilitating the development of fairer employment, this paper addressed the career barriers of Arab women managers by linking several macro-level factors (most notably, the gendered national legislative systems and the intersection between Isalm, Urf and patriarchy), with organizational-level factors (e.g., governance system and HR policies and practices), and micro-level factors (e.g., women mangers' perceived traits). The findings of the present research validated the findings of Karam and Afioni (2013), Keeton (1996), Budworth and Man (2010), Metcalf (2011), the WB (2014) and UNDP (2013). Consistent with previous research findings is the analogy revealed by the present findings between the Arab women managers' challenges inside their organizations (i.e., at the mezzo level) and those facing them outside the organization (i.e., at the macro level).…”
Section: Secondsupporting
confidence: 88%
“…Further, the literature (e.g., Broadbridge & Hearn, 2008;Broadbridge & Simposon, 2011) suggests that the majority of women, regardless of their organizational level, attribute success primarily to factors within their purview (e.g., merit and effort), followed by the socio-psychological factors, (Keeton, 1996). In this respect, Broadbridge, (2008), Broadbridge and Hearn, (2008), and Budworth and Mann, (2010) explained that a good track record (professional portfolio and hard work) may enable women to partially overcome the negative consequences of gender related socio-psychological and systematic factors (e.g., negative gender stereotypes in male gender-typed positions).…”
Section: Brief Review Of Non-arab Researchmentioning
confidence: 99%
“…Second, women who rise to leadership positions in male‐dominated organizations are inclined to preserve the organizational culture that is perceived to have served them well and allowed them to thrive in the organization (Gibson and Cordova ). Third, when the share of leadership positions held by women is few, women in those positions are likely to see other women as competitors for scarce resources and exhibit a reluctance to train, mentor, and support women below them in the hierarchy (Keeton ).…”
Section: The Theory Of Representative Bureaucracymentioning
confidence: 99%
“…women as competitors for scarce resources and exhibit a reluctance to train, mentor, and support women below them in the hierarchy (Keeton 1996).…”
Section: Active Racial and Gender Representationmentioning
confidence: 99%
See 1 more Smart Citation